The Double Burden of COVID-19 and Dengue in Nepal: The challenges ahead - Pandey, K.; Dumre, S. P.; Dhimal, M.; Pun, S. B.; Shah, Y.; Fernandez, S.; Morita, K.; Pandey, B. D. (Kathmandu University Medical Journal, 2021)
Coronavirus disease 2019 (COVID-19) pandemic has caused significant impact on the health care system. As a consequence, diagnosis and treatment of vector borne diseases including dengue has been equally affected. Nepal is no exception to this, where COVID-19 cases is exponentially increased and all resources are concentrated on its prevention, control and management. Dengue, one of the major vector-borne diseases in Nepal, is apparently overlooked despite approaching the peak season of the disease. The aim of this paper is to describe the double burden of COVID-19 and dengue in Nepal, particularly highlighting the co-circulation and possible coinfections. This has posed higher risk of increased severity, more severe cases and deaths in Nepal. Moreover, potential misdiagnosis of these viral diseases may lead to delayed or, inappropriate treatment and poor allocation of resources.